An annotated and illustrated catalog of the primary type material of Hemiptera deposited in the Florida State Collection of Arthropods - Powell, Erin C.; Halbert, Susan E.; Deeter, Lily; Keller, Oliver (Zootaxa, 2023)
The Florida State Collection of Arthropods (FSCA) is one of the largest and most diverse insect collections in North America and the largest in the southeastern United States with over twelve million curated specimens and significant amounts of materials in bulk collections and other unprocessed samples. The order Hemiptera currently comprises approximately 95,000 species in three suborders. The FSCA houses type material in the auchenorrhynchan families Cicadidae, Cicadellidae, Cixiidae, Delphacidae, Derbidae, and Membracidae; the heteropteran families Coreidae, Corixidae, Curaliidae, Lygaeidae, Miridae, Pentatomidae, Reduviidae, Schizopteridae, Scutelleridae, and Tingidae; the sternorrhynchan families Aleyrodidae, Aphalaridae, Aphididae, Coccidae, Diaspididae, Matsucoccidae, Pseudococcidae, Phacopteronidae, and Triozidae. This catalog documents the FSCA primary type material for 167 species in 79 genera in 24 families across the three suborders.